Control of Unipolar/Ambipolar Transport in Single‐Molecule Transistors through Interface Engineering. (13th April 2020) - Xin, Na; Kong, Xianghua; Zhang, Yu‐Peng; Jia, Chuancheng; Liu, Lei; Gong, Yao; Zhang, Weining; Wang, Shuopei; Zhang, Guangyu; Zhang, Hao‐Li; Guo, Hong; Guo, Xuefeng
Abstract: To realize single‐molecule field‐effect transistors, a crucial test for evaluating the integrity of single‐molecule electronics into conventional circuit architectures, remains elusive. Though interfacial effect is widely accepted to be crucially important in electronic devices, rare reports have studied fine control of the interface in single‐molecule transistors. Through molecular engineering, different numbers of methylene groups are incorporated between the diketopyrrolopyrrole (DPP) kernel and anchor groups (AMn‐DPP, n = 0−3), and how the molecule–electrode interface affects the performance of single‐molecule transistors is investigated. Both experimental and theoretical data demonstrate that p‐type charge transport dominates in AM0‐DPP and AM1‐DPP single‐molecule transistors, while AM2‐DPP and AM3‐DPP systems exhibit ambipolar field‐effect behaviors, which is attributed to the HOMO‐pinning effect in AM0‐DPP and AM1‐DPP molecular junctions. Theoretical calculations show that the parity of the methylene number results in two different connection symmetries between the DPP kernel and graphene electrodes, and thus different electronic interactions, leading to different relative molecular energy‐level alignments form those of isolated molecules, which has never been reported before. These results provide crucial information for precise control of the interfaces in molecular junctions, new insight into building multifunctional graphene–organic hybrid electronic devices, and the design of functional organic materials. Abstract : Through molecular engineering, a series of diketopyrrolopyrrole derivatives with different numbers of methylene groups are sandwiched between nanogapped graphene electrodes to systematically investigate how the contact interface affects the performance of single‐molecule transistors. In addition, the parity of the methylene number results in two different connection styles and different molecular energy‐level alignments, thus leading to efficient gate‐regulated conductance characteristics.